Leisure-time centres in Iceland - Germina Kharlanova 1988- (2016)
This theoretical project arises important questions about leisure-time centres in Iceland. This work is a product of personal experience in the field of after school care programs and research database. This project has an aim to explore the work of leisure-time centres in Reykjavik and to look at different aspects of such centres in general. The main significance of the study is to explain the importance of such types of after school organizations in Reykjavik, and also to maintain the work of recreation personnel, who puts a lot of efforts for making children’s staying in leisure centres comfortable and enjoyable. Findings of this study show that leisure-time centres in Iceland are essential elements in children’ lives of Icelandic origin and non-Icelandic origin, Icelandic parents’ and immigrant parents’ lives, children with special needs and people working in such organizations. My work experience in after school centre helped me to reveal strong and weak sides of leisure-time organizations in Reykjavik, so this study can be useful for future research in this field.